PENERAPAN COOPERATIVE LEARNING TIPE TGT DALAM PEMBELAJARAN TENIS LAPANGAN TERHADAP SIKAP EMPATI DAN KEMAMPUAN PUKULAN FORHAND DRIVE MAHASISWA UNIVERSITAS PGRI PONTIANAK - Hartanto, Dwi; Dewi, Utami (Jurnal Pendidikan Olah Raga, 2025)
This study aims to examine the application of the Cooperative Learning learning model of the Teams Games Tournament (TGT) type in tennis courses and its effect on empathy of students at Universitas PGRI Pontianak. The TGT model, which emphasizes teamwork through game-based competition, is applied to improve social interaction, cooperation, and mutual respect among students. The research method uses a quantitative approach with a quasi-experimental design. The research sample was students taking tennis courses, who were selected purposively. The research instruments included observation, empathy questionnaires, and tennis skills tests. The results showed that the application of the TGT model not only improved tennis skills but also significantly strengthened students' empathy attitudes, such as the ability to understand other people's feelings, tolerance, and teamwork. Thus, TGT type Cooperative Learning has proven effective in integrating motor skills learning with social character development in students.